Moulding add-on systems - Balasubramaniam, Varatharajan (2018)
The term injection moulding process has been in use for nearly 150years. However, it has already become the most important method in plastic processing techniques. This injection moulding process comprises of mechanical, electrical, hydraulic, thermal and automation systems. This report mainly deals with few parts of injection moulding system and majorly add-on parts for the injection moulding machine and few areas of the automation for the add-on systems. These add-on systems make the moulding process efficient, sustainable and profitable. Due to an increase in innovative ideas in the moulding system, it has helped to attain new heights in the manufacturing process. The scope and development of the mould and its dependent systems are rapidly increasing. Some of the add-on systems are multi-purpose and helps to decrease the production time of the product. This report also deals with the solution for the problems encountered in various parts of the add-on systems.